Vitamin D level and its association with adiposity among multi ethnic teachers in Wilayah Persekutuan Kuala Lumpur, Malaysia / Intan Shafinaz Sharifudin - Intan Shafinaz , Sharifudin (2016)
Vitamin D plays an essential role in health. Its deficiency can not only increase the risk of osteoporosis, but also contribute to cardiovascular diseases, diabetes and certain types of cancers. Skin synthesis of vitamin D from sunlight exposure constitutes the major source of vitamin D. Evidences showed that not only temperate countries experience the problem of vitamin D deficiency, but a similar problem exists in tropical countries like Malaysia, Indonesia, Saudi Arabia and Tehran. Currently, there are new evidences that show obesity may contribute to vitamin D deficiency. Obesity-associated vitamin D deficiency is most likely due to the decreased bioavailability of vitamin D3 because of its deposition in the body fat compartments. The aim of this study was to identify the risk factors contributing to a low serum 25(OH)D level and its association with adiposity among secondary school teachers in the state of Wilayah Persekutuan Kuala Lumpur (WPKL). This was a cross sectional study of two-stage sampling conducted from February 2013 to May 2013. First, 50% out of a total of 80 government day schools in WPKL were randomly selected from each district in Pudu, Bangsar, Sentul and Keramat respectively. Then, all teachers from the selected schools who fulfilled the inclusion criteria of the study were invited to participate. Ethics clearance was obtained from the University Malaya Medical Centre (UMMC) Ethics Committee (Reference Number: 950.1). Approval from the Ministry of Education, Education Board of Wilayah Persekutuan Kuala Lumpur (WPKL) and principals from each selected schools were obtained before data collection. Informed consent was obtained from all participants. The data collection included serum 25 hydroxyvitamin D (25(OH)D), Parathyroid Hormone (PTH), blood glucose, fat percentage, waist circumference and Body Mass Index (BMI). Demographic iii characteristics, sun exposure and avoidance, and level of physical activity were also collected using a self-administered questionnaire. A total of 858 participants were recruited. The majority of them were Malays, females and married. The overall prevalence of vitamin D deficiency (<20 ng/ml) was 67.4%. Indian (80.9%) participants had the highest proportion of vitamin D deficiency, followed by Malays (75.6%), others (44.9%) and Chinese (25.1%). There was a significant negative association between serum 25(OH)D level with BMI (β= -0.23) and body fat percentage (β= -0.14). In the multivariate linear regression analysis; Malays, Indians, females (p<0.001), higher BMI and larger waist circumference (p<0.05) were significantly associated with lower serum 25(OH)D level. The full model explained 32.8% of variation contributing to serum 25(OH)D level among the participants. Adiposity explained only less than 1% of the variability of serum 25(OH)D level. The two most influential factors affecting serum 25(OH)D level were ethnicity and sex. Health education should be targeted in weight management, sex based behaviors on sun exposure and avoidance, as skin pigmentation is non-modifiable.